(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2006)
This papaer had as its support the cognitive behavioral therapy. Its objective was to investigate if and how the negative emotional state can led the individual to develop negative responses, making possible the construction of dysfunctional behaviors, such as the action of smoking. The participant, of this study was a male, adult, and he became dependent of nicotine through thirty years of use. This way, the action of smoking was endangering his health. He was submitted to the psychotherapeutic intervention, focused in the control of his anxiety and of the non-adapted behaviors. The obtained results demonstrated that the proposed intervention, for this case study, was effective: there was been decreased in more than 90% of the behavior of smoking, the reduction of the anxiety and the increase of assertive behavior. It was concluded that the defined psychoterapeutic process aided in the improvement of the quality of the client’s life.